The Effect of Tax Relaxation, Tax Sanctions, and Gender on Two-Wheeled Motorized Vehicle Taxpayer Compliance at UPPD Samsat Banjarmasin II - Zaini, Siti Aisyah Mukarramah; Syahdan, Saifhul Anuar; Ruwanti, Gemi; Boedi, Soelistijono (Asosiasi Dosen Akuntansi Indonesia, 2024)
This research aims to empirically test the effect of tax relaxation, tax sanctions, and gender on taxpayer compliance for two-wheeled motorized vehicles at UPPD Samsat Banjarmasin II.This quantitative research employs questionnaire as data collection method. Further, 70 two-wheeled motor vehicle taxpayer registered with UPPD Samasat Banjarmasin II are chosen as the respondents. The hypothesis testing in this research uses multiple linear regression analysis. The results of this research show that tax sanctions have an effect on taxpayer compliance for two-wheeled motorized vehicles at UPPD Samsat Banjarmasin II. Meanwhile, tax relaxation and gender have no effect on taxpayer compliance for two- wheeled motorized vehicles at UPPD Samsat Banjarmasin II. Moreover, there is no differences in vehicle taxpayer compliance motorized two-wheelers based on gender